2016
DOI: 10.1120/jacmp.v17i6.6455
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a GPU‐based Monte Carlo dose calculation algorithm in the Monaco treatment planning system

Abstract: A new GPU‐based Monte Carlo dose calculation algorithm (GPUMCD), developed by the vendor Elekta for the Monaco treatment planning system (TPS), is capable of modeling dose for both a standard linear accelerator and an Elekta MRI linear accelerator. We have experimentally evaluated this algorithm for a standard Elekta Agility linear accelerator. A beam model was developed in the Monaco TPS (research version 5.09.06) using the commissioned beam data for a 6 MV Agility linac. A heterogeneous phantom representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…The Graphics Processing Unit Monte Carlo Dose (GPUMCD) calculation algorithm used in the Monaco TPS has been verified to some extent by comparison with independent Monte Carlo algorithms and film measurements. However, given that our results indicate that small volumes on or close to the surface of curved air–tissue boundaries could increase risk of toxicity, the accuracy of the TPS dose calculation for small volumes on density boundaries should be verified …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Graphics Processing Unit Monte Carlo Dose (GPUMCD) calculation algorithm used in the Monaco TPS has been verified to some extent by comparison with independent Monte Carlo algorithms and film measurements. However, given that our results indicate that small volumes on or close to the surface of curved air–tissue boundaries could increase risk of toxicity, the accuracy of the TPS dose calculation for small volumes on density boundaries should be verified …”
Section: Discussionmentioning
confidence: 94%
“…However, given that our results indicate that small volumes on or close to the surface of curved air-tissue boundaries could increase risk of toxicity, the accuracy of the TPS dose calculation for small volumes on density boundaries should be verified. 45,46 The air-tissue transition gradient in the image used for dose calculation should also be noted when considering the TPS accuracy around air cavities. Uilkema et al found that dose effects of ERE were 20% smaller when calculated using a four voxel air-tissue transition, similar to our study (although different size voxels), compared to an abrupt transition.…”
Section: B Tps Accuracymentioning
confidence: 99%
“…Several publications have considered individual aspects of QA on MR-linac devices. Measurement equipment performance, [10][11][12][13][14][15][16][17][18] reference 19 and relative 15,[20][21][22][23] dosimetry within the presence of a magnetic field, treatment planning system, [24][25][26][27][28] Linac, 22,[29][30][31] MR device commissioning, 32,33 and routine QA 32,[34][35][36][37] are the broad range of areas addressed. While not considerably different to conventional RT QA, there are several aspects that need considering.…”
Section: Introductionmentioning
confidence: 99%
“…We searched articles available to the public from multiple journals concerning lung phantoms. Although a number of phantoms have been tested, including solid water, cork and solid water, balsa wood and solid water, balsa wood and cork, cork and plastic, cork and acrylic, polystyrene and cork, bolus and sponge, foam, and even wood, it appears that we are the first to report open‐access on the use of a cork‐and‐animal‐tissue lung tumor phantom.…”
Section: Introductionmentioning
confidence: 99%